Some Essensial Aspects of Arbitration and Access to Justice - Ruiz, Ivan Aparecido (2010)
In the context of the Brazilian judicial reality, it is imperative and urgent to revive and leverage new ways of resolving interest conflicts. Stands out in this work, the mechanism of arbitration, which since September 23, 1996 gained new contours with the enactment of Law No. 9307. Modern legal diploma writing has brought great advances to the institute, but even after thirteen years after its issue, the arbitration expansion regarding its use, goes through hard times in the Brazilian legal system. This study has the didactic intention of studying the key aspects of the Institute and can see how the arbitration may be, beyond an effective means of resolving interest conflicts, it also plays its role as an instrument for achieving access justice, law and fundamental guarantee of any person.